Optimization of Surgical Management in Postoperative Bile Leakage and Bilic Peritonitis After Cholecystectomy - Arziev Ismoil Alievich; Kurbaniyazov Zafar Babazhanovich; Sayinaev Farrukh Karamatovich; Baratov Manon Bakhramovich; Nazarov Zokir Norzhigitovich (Zien Journals, 2022)
This study analyses the results of surgical treatment of 3266 patients with various forms of cholelithiasis. Biliary leakage and biliary peritonitis in the postoperative period were observed in 34 patients due to "minor" damages (aberrant hepatic and urinary ducts of the gallbladder bed - Luschka's passage, leaky stump of the gallbladder duct, drainage falling out of the choledoch). Improved surgical tactics based on ultrasound and RCCG data facilitated improvement of treatment results and avoiding relaparotomy in 94,2% of cases with bile leakage with "minor" bile duct injuries.
Keywords: cholecystectomy; biliary leakage; biliary peritonitis; surgical tactics